Kuliwa: A Cultural Identity of the Local People of Mandar, West Sulawesi - Zuhriah, Zuhriah (Universitas Islam Negeri Raden Mas Said Surakarta, 2016)
Tola’ bala means to refuse or to draw away the danger that might happen. In West Sulawesi it is called Kuliwa. It is being done by the wife of fisherman, punggawa’. The people of Mandar are usually practicing kuliwa ritual before going to fishing or venturing to a journey through the sea. It is an obliged ritual, which is done for inaugurating or welcoming something as in object or through ceremonial acts. For instance, to inaugurate the use and first voyage of a ship, or to acquire machine or other tools used for fishing (jala and gae’), and for the first time for fishing. It is requirement ritual for every fisherman before having a long journey into the sea. They believed that without practicing Kuliwa, something dangerous in the sea might happen during the sailing time. Hereby, this paper aims to explore more on what the way of the people of Mandar is still practicing and maintaining this ritual and how it becomes gather in tradition and religion? Kuliwa is not just talking about tradition, but also the life of religion in Mandar society and further believed as their cultural identity.